2006
DOI: 10.1073/pnas.0603090103
|View full text |Cite
|
Sign up to set email alerts
|

Alternative inclusion of fibroblast growth factor receptor 2 exon IIIc in Dunning prostate tumors reveals unexpected epithelial mesenchymal plasticity

Abstract: In epithelial cells, alternative splicing of fibroblast growth factor receptor 2 (FGFR2) transcripts leads to the expression of the FGFR2(IIIb) isoform, whereas in mesenchymal cells, the same process results in the synthesis of FGFR2(IIIc). Expression of the FGFR2(IIIc) isoform during prostate tumor progression suggests a disruption of the epithelial character of these tumors. To visualize the use of FGFR2 exon IIIc in prostate AT3 tumors in syngeneic rats, we constructed minigene constructs that report on alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 41 publications
8
107
0
Order By: Relevance
“…This is consistent with findings in clinical material, in which membranous E-cadherin was detected in hepatic metastasis using immunohistochemistry, and vimentin was absent in the tumor cells. In the Dunning prostate cancer model, mapping of FGF receptor-2 splice variant expression demonstrated the occurrence of METs (indicated by co-expression of E-cadherin and FGF receptor-2(IIIb)) in primary tumors, typically where the tumor cells were in contact with the stroma (Oltean et al, 2006). In lung micrometastases, tumor cells in contact with the lung parenchyma and adjacent to blood vessels also frequently underwent MET.…”
Section: Met In Cancer Progression and Metastasismentioning
confidence: 99%
“…This is consistent with findings in clinical material, in which membranous E-cadherin was detected in hepatic metastasis using immunohistochemistry, and vimentin was absent in the tumor cells. In the Dunning prostate cancer model, mapping of FGF receptor-2 splice variant expression demonstrated the occurrence of METs (indicated by co-expression of E-cadherin and FGF receptor-2(IIIb)) in primary tumors, typically where the tumor cells were in contact with the stroma (Oltean et al, 2006). In lung micrometastases, tumor cells in contact with the lung parenchyma and adjacent to blood vessels also frequently underwent MET.…”
Section: Met In Cancer Progression and Metastasismentioning
confidence: 99%
“…Several transcription factors, including zinc finger proteins of the Snail and Twist families (e.g., dEF1/ZEB1/ TCF8 and SIP1/ZEB2/ZFHX1B) and the basic helix-loophelix factor E12/E47, which have been shown to be associated with the repression of E-cadherin (22), are also depressed during MET. As described above, downregulation of ZEB1, Slug, Snail, SMA, or Twist is usually induced during MET (49,61,64).…”
Section: Transcriptional Factorsmentioning
confidence: 99%
“…By using the bladder carcinoma TSU-Pr1 (T24) progression series of cell lines selected in vivo via systemic seeding, Chaffer and colleagues (21) showed the importance of the epithelial phenotype in the formation of secondary tumors, as epithelial characteristics were dramatically associated with increased bone and soft-tissue colonization after intracardiac or intratibial injection. Furthermore, Oltean and colleagues (22,23) observed an unexpected MET among lung micrometastases in the organ parenchyma and immediately adjacent to blood vessels by visualizing the fibroblast growth factor receptor-2 (FGFR2) exon IIIc in a prostate cancer model. In addition, non-EMT hamster cheek pouch carcinoma-1 cells, but not EMT cells, were found to be able to form overt lung metastases after being inoculated into the bloodstream by tail-vein injection (24), suggesting that EMT is not conducive to the formation of metastases and that EMT cells in vivo might possibly be converted into the non-EMT cells via MET at the site of metastases.…”
Section: Association Of Met With Metastatic Tumor Formationmentioning
confidence: 99%
“…To examine FGFR2 splicing in vivo, Garcia-Blanco and colleagues (Oltean et al 2006) developed a minigene reporter system designed to express RFP in cells in which exon IIIc is not included. They injected mesenchymal AT3 prostate tumor cells expressing the minigene into mice and found that, after invading the lungs, the tumor cells frequently exhibited IIIc skipping, indicative of a mesenchymal-to-epithelial transition (MET), which was confirmed by the presence of the epithelial marker E-cadherin.…”
Section: Fgfrsmentioning
confidence: 99%